Transformasi Estetika Seni Lukis ke Instalasi dalam Praktik Seni Rupa Kontemporer Indonesia: Studi Karya Agung Tato Suryanto - Reny Catur Wulandari; Anik Juwariyah; Trisakti Trisakti; Indar Sabri (Jurnal Impresi Indonesia, 2025)
This study explores the aesthetic transformation from painting to installation art within the context of contemporary Indonesian art through a case study of Agung Tato Suryanto's works. This transformation signifies not only a shift in medium from two-dimensional to three-dimensional formats but also a paradigmatic change in how artists convey aesthetic, symbolic, and philosophical ideas. Using a qualitative method and case study approach, this research examines two key works—Second Level as a painting and Lingga Bergema as an installation—through the lens of Immanuel Kant’s aesthetic theory, Roland Barthes’ semiotics, and Theodor Adorno’s critical aesthetics. The analysis reveals that Agung Tato constructs a visual language that critically reflects on the dehumanizing and disoriented nature of modern urban life. In Second Level, he explores the absence of human presence in urban architecture as a metaphor for existential alienation, while in Lingga Bergema, he deconstructs patriarchal cultural symbols through reflective spatial installation. Both works expand aesthetic experience beyond the visual to become multisensory and participatory. This study concludes that Agung Tato’s aesthetic transformation is a conceptual strategy that responds to the complexities of contemporary social reality, demonstrating that contemporary art is no longer merely a visual object, but a dialectical space for critical consciousness, open interpretation, and deep aesthetic engagement.